Genetic determinants of daytime napping and effects on cardiometabolic health - Hassan S. Dashti (Nature Portfolio, 2021)
The genetic basis of daytime napping and the directional effect of daytime napping on cardiometabolic health are unknown. Here, the authors perform a genome-wide association study on self-reported daytime napping in the UK Biobank and Mendelian randomization to explore causal associations.